Traumatic Response Of Children Flood Victims In Jayapura District, Papua - Suweni, Korinus; Kristina, Yunita; Felle, Zeth Robert; Apay, Frengki; Tafor, Demianus (International Journal of Psychosocial Rehabilitation, 2020)
Floods are one of the natural disasters that often occur in Indonesia. Floods can occur due to high rainfall. victims from groups of children are the most vulnerable groups who are victims and suffer the most from adults. The National Disaster Management Agency (BNPB) noted, during 2018 there were 1,999 disaster events in Indonesia. In terms of the number of disasters in 2018, the number of disasters in 2016 was 2,392 and 2017 were 2,392. Knowing the traumatic response of children victims of banjir bandang in JAYAPURA district of Papua. Qualitative method with phenomenology approach. The number of participants in this study were six participants. In data analysis using inductive thinking methods. The results of the study concluded four themes about the traumatic response of children victims of banjir bandang. The themes identified were: psychological responses, cognitive responses, physical responses, changes in social relations.